ACTIVE LEARNING BERBANTUAN FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI VEKTOR - Padrul Jana; Andreast Wahyu Sugiyarta (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This research aims to apply Active Learning with Flashcard assisted and to improve learning outcomes in vector material for students of X MIPA 3 Muhammadiyah 3 Yogyakarta Senior High School. This research is a Classroom Action Research (CAR). The subjects of this research were students of class X MIPA 3 as many as 32 students. The subject of this class action research because based on observations made by the teacher during the learning process, students were still very less active. Data collection techniques are carried out by observation, tests, and documentation. The results showed that there was an increase seen from the percentage of learning completeness. Learning completeness experienced a significant increase. In the initial condition, the percentage was 28.13% then increased at the end of Cycle I to 40.63% meaning that flashcard-assisted active learning can improve student learning outcomes but still not reach the target of 80% so that it continues in Cycle II. At the end of Cycle II, there was another more significant increase to 100%, meaning that flashcard-assisted active learning is very suitable to be applied to improve learning outcomes. Thus it can be concluded that the use of Active learning models with Flashcard assisted can improve the activity and learning outcomes. This learning model can be used as an alternative for mathematics teachers in doing classroom learning creativity.